PENENTUAN KUALITAS KARET BERDASARKAN DIVISI MENGGUNAKAN METODE MOORA - Nurwati Nurwati; William Ramdhan; Dewi Maharani (Smart Education, 2022)
The System in an element that interacts with each other to achieve a goal, gathered together to process or to complete certain goals. At PT. BspGurach Batu Estate Tbk. Determination of the best rubber quality by division is a process in the progress of its business field so that customers are satisfied with the quality of the processed rubber. The methodology used is the quantitative method where this method contains the calculation of the processed data. The MOORA method is a method that is applied to solve problems with complex mathematical calculations introduced by Brauers and Zavadskas in 2006 with the DSS, which is to support decision makers in choosing alternative decisions which are the result of alternative data processing based on the criteria used and obtain results where Alternative 3 (A3) as the highest alternative for quality rubber. With a decision support system made using the Multi-Objective Optimization by Ratio Analysis (MOORA) method, it can assist in the decision-making process for determining rubber quality based on the division that has rubber quality.